2009
DOI: 10.1128/jvi.01703-08
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Importance of the Adenovirus E4orf4 Protein during Lytic Infection

Abstract: The human adenovirus type 5 (Ad5) E4orf4 product has been studied extensively although in most cases as expressed from vectors in the absence of other viral products. Thus, relatively little is known about its role in the context of an adenovirus infection. Although considerable earlier work had indicated that the E4orf4 protein is not essential for replication, a recent study using dl359, an Ad5 mutant believed to produce a nonfunctional E4orf4 protein, suggested that E4orf4 is essential for virus growth in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Consistent with previous reports, the virus mutant Hpm4166 (lacking E4orf4) exhibited modestly higher E4orf6 protein expression (Fig. 2A, lane 4) (47) and therefore resulted in more efficient coimmunoprecipitation with endogenous HoxB7 (Fig. 2A, upper panel, lane 4).…”
Section: E4orf6 Interaction With Hoxb7supporting
confidence: 79%
“…Consistent with previous reports, the virus mutant Hpm4166 (lacking E4orf4) exhibited modestly higher E4orf6 protein expression (Fig. 2A, lane 4) (47) and therefore resulted in more efficient coimmunoprecipitation with endogenous HoxB7 (Fig. 2A, upper panel, lane 4).…”
Section: E4orf6 Interaction With Hoxb7supporting
confidence: 79%
“…It has been known for some time that adenovirus infection has a profound effect on the processing and export of rRNA as well as affecting nucleolar antigens [83]. More recently, we and others have reported on adenovirus proteins that are directed to the nucleolus and on the sequestration of nucleolar antigens B23.1, B23.2, nucleolin and UBF into viral replication centres [47,48,[84][85][86][87][88][89][90][91][92]. Most notably, we showed that UBF was functionally recruited into viral DNA replication centres apparently without affecting the function of RNA pol I.…”
Section: Nucleolar Proteomics and Viral Infectionmentioning
confidence: 92%
“…However, it has not yet been shown that this regulation of the APC occurs during adenovirus infection. E4orf4 is nonessential for virus replication in cultured human cancer or primary cells, so how this protein impacts adenovirus biology remains elusive (41). Determining whether E4orf4 inhibits the APC during infection, elucidating its consequence on virus replication, and identifying its mechanism of action are key questions to address in future studies.…”
Section: Modulation Of the Apc By Virusesmentioning
confidence: 99%